Studies in Nietzsche and the Judaeo-Christian Tradition - O'Flaherty, James C.; Sellner, Timothy F.; Helm, Robert M. (UNC Studies in the Germanic Languages and Literatures, 1985)
This collection of essays is a sequel to the editors' 1976 volume "Studies in Nietzsche and the Classical Tradition". Philosophers, theologians, and literary historians discuss important aspects of Nietzsche's attack on Judaism and Christianity. The book contains studies of his view of biblical figures, Luther and Pascal as well as comparisons of his thought with that of Spinoza, Lessing, Heine, and Kierkegaard. Nietzsche's critique of the Old Testament, the Jewish religion of the diaspora, and historical Christianity are also investigated. Of the eighteen articles included here, thirteen were prepared expressly for this volume-five were translated from German, one from French, and one from Hebrew. Contributors to this volume are: Eugen Biser, Harry Neumann, Israel Eldad, Charles Lewis, Jorg Salaquarda, Joan Stambaugh, Max L. Baeumer, Brendan Donellan, Diana Behler, Sander L. Gilman, Gerd-Gunther Grau, Josef Simon, James C. O'Flaherty, Bernd Magnus, Georges Goedert, Hans Lung, and Karl Barth.